1985
DOI: 10.1038/jcbfm.1985.52
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Atrophy and Hypoperfusion Improve during Treatment of Wernicke-Korsakoff Syndrome

Abstract: Nineteen patients with sudden onset of impaired recent memory, cerebellar ataxia, peripheral neuropathy, and other signs of Wernicke-Korsakoff syndrome (WKS) were treated and examined prospectively for 3 months. Serial studies included histories, neurological examinations, cognitive capacity screening examinations (CCSE), computed tomography (CT) scans, and measurements of regional CBF. Patients were detoxified and withdrawn from sedatives before CBF measurements were examined. Treatment included alcohol withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…These observations are consonant with neuropathological studies indicating that part of the age-related leukoaraiosis may be secondary to decreased synaptic density with neuronal shrinkage and/or loss [14,15], which may be exacerbated by ischemia [16] and alcohol abuse [17,18]. CT changes associated with normal aging include progressive cerebrocortical atrophy, with polio-and leukoaraiosis, all of which are coupled with perfusional decline compatible with progressive neuronal and synaptic degenerative changes with decreased cerebral metabolic demands [6,14,15,19,20].…”
Section: Commentarysupporting
confidence: 58%
See 1 more Smart Citation
“…These observations are consonant with neuropathological studies indicating that part of the age-related leukoaraiosis may be secondary to decreased synaptic density with neuronal shrinkage and/or loss [14,15], which may be exacerbated by ischemia [16] and alcohol abuse [17,18]. CT changes associated with normal aging include progressive cerebrocortical atrophy, with polio-and leukoaraiosis, all of which are coupled with perfusional decline compatible with progressive neuronal and synaptic degenerative changes with decreased cerebral metabolic demands [6,14,15,19,20].…”
Section: Commentarysupporting
confidence: 58%
“…Leukoaraiosis is known to be age-related [6,[31][32][33][34][35][36], aggravated by hypertension [36], episodic hypotension [37], heart Meyer/Terayama/Konno/Akiyama/ Margishvili/Mortel disease, diabetes mellitus, heavy alcohol consumption [17][18][19], and strokes, particularly lacunes [16,38]. Among elderly demented and nondemented subjects, leukoaraiosis has been correlated with advancing age, cerebral atrophy, hypoperfusion of white matter and cognitive impairments [39].…”
Section: Commentarymentioning
confidence: 99%
“…Loss of structural lipids of myelin and decreased concen trations of cerebrosides and phospholipids have been described in chronic alcoholic individuals at autopsy (Lesch et a!., 1972;Alling and Bostrom, 1980). In a previous study of Wernicke-Korsakoff syndrome from this laboratory, significant reduc tions of white matter flow were found (Meyer et a!., 1985). The present results were compared with those obtained previously in Wernicke-Korsakoff syndrome, and it was concluded that thiamine de ficiency appears to play a major role in decreasing white matter flow.…”
Section: Discussion Brain Volume Measurements In Chronic Alcoholic Pasupporting
confidence: 63%
“…In developed countries, poor nutrition in the context of severe chronic alcoholism is the leading cause of this disease. 99 The primary clinical symptom is profound recent memory loss and an ensuing anterograde amnesia. KD is often preceded by acute Wernicke's encephalopathy, which is a clinical state consisting of ataxia, incoordination, ocular disturbances, and mental confusion resulting from a nutritional thiamine deficiency.…”
Section: Wernicke-korsakoff 'S Syndromementioning
confidence: 99%